The personification metaphor as a measurement instrument approach for corporate reputation - Davies, G.; Chun, R.; Vinhas da Silva, R.; Roper, S. (Corporate Reputation Review, 2001)
Many existing approaches to the measurement of corporate reputation have been criticized as being overly focused on the financial performance of companies and on the views of external stakeholders. Further, there is as yet no established universal measure to assess both the internal (often referred to as identity) and external (often referred to as image) elements of reputation. A number of models of reputation see these two elements as interlinked. It follows that any comprehensive measurement tool for reputation should be applicable both inside and outside of the organization. This paper addresses the potential for the personification metaphor as a measurement strategy in the assessment of both the internal and external facets of reputation. Its purpose is to apply the personification metaphor to the measurement issue and to formalize the approach using an established methodology. Empirical evidence is provided of data from three companies, each in a different sector: retailing, financial services and business-to-business. The personality framework and validated scales of Aaker (1997) are used to assess the identity and image of each company. The data are used to demonstrate significant linkages between image and identity and the ability of the scales to identify differences between the images and identities of different organizations. While we conclude that there is merit in the application of the personality metaphor to the issue of the measurement of reputation, a number of weaknesses in using the one existing scale are identified, including items that are culturally specific. Consequently, the reliability measures achieved are not as high here as in the original work. Further research is envisaged to develop scales that are of greater efficacy in the field of reputation.